The effectiveness of artificial intelligence health education accurately linking system on self-management in non-specific lower back pain patients - Li, Yun-Hua; Li, Na; Liu, Zhi-xia; Du, Shuang; Shuai, Yujiang; Yang, Renjun; Xu, Lei; Li, Xiaoyan; Jiang, Yang; Li, Wenwen (Frontiers in Public Health, 2025)
BackgroundIntegrating artificial intelligence (AI) with mobile health is revolutionizing chronic disease management. Non-specific lower back pain (NSLBP), a leading worldwide disabling condition, negatively impairs patient quality of life and psychological status. Standard treatments, mostly pharmacological and physiotherapies, do not offer long-term support for self-management. Consequently, we developed the AI-Health Education Accurately Linking System (AI-HEALS) to investigate its application in improving self-management, alleviating pain, and enhancing overall life quality for NSLBP patients.MethodsThis study utilizes a randomized controlled trial (RCT) to evaluate the effectiveness of a three-month AI-HEALS intervention in improving self-management among patients with NSLBP. Participants are randomly assigned to either a control group receiving standard care or an intervention group receiving standard care supplemented by the AI-HEALS program. The intervention features an AI-powered, voice-activated interactive Q&A system, along with physiological monitoring, regular reminders, and tailored educational content. These services are primarily delivered via a WeChat official account titled “NSLBP Health Management Expert.” The AI-HEALS system builds its knowledge base based on NSLBP treatment guidelines to ensure the accuracy and reliability of the information provided. The primary outcome measure is pain intensity, while secondary outcomes assess self-management behaviors, psychological well-being, and physiological parameters.DiscussionAI-HEALS program combines AI with mobile health to provide an organized platform for efficient home care of NSLBP, alleviating pain, enhancing quality of life, and lessening dependency upon conventional medical resources. Results from this study will establish AI-HEALS’ effectiveness in managing chronic diseases and provide a science basis for subsequent health intervention.Clinical trial registrationIdentifier, CHICTR2400090707.